Mâtürîdî’nin Meleklerin Varlığına Dair Görüşlerinin Değerlendirilmesi - Kardaş, Atike (TSBS Bildiriler Dergisi, 2021)
Existences in Kalām’s literature are divided into two; the Eternal without beginning of existence and subsequently occurring the existent in time. The Eternal is Allah himself, who does not have the characteristics of creation, being later, or being born. The existent in time is everything except Allah. The existent in time existences are examined in two parts as latīf (transparent) and kasīf (solid). The kasīf existences that make up the universe we live in are divided into two clusters: live and lifeless; lifelesses are also divided into two subsets in the form of liquid-solid. It is out of the question to discuss their existence because the physical senses can just perceive these. Latīf existences that make up the invisible universe are divided as ulwī (lofty) and suflī (servile). Angels are under the ulvī division. There are disputes about existence of angels because angels don’t appear as kāsīf existences. Angels are beings of the invisible universe; they cannot be perceived by our senses. Therefore, positive sciences, which come to a conclusion with experiment and experience, are not concerned with the existence and absence of angels. We reach information about them from the Qur’ān and the hadiths. To believe in the existence of angels in the Qur’ān is considered among the principles of faith. In addition, without being under any influence, sound mind judges the existence of angels. Believing in the existence of Angels is fixed by texts, but while some alims are trying to prove their existence with rational proofs, some think that the text evidence proves their existence. In this rescript, Abū Mansūr al-Māturīdī’s (d. 333/944) books named Kitāb al-Tawhīd’s and Ta’wīlāt al-Qur’ān were taken into the center, and his view on the existence of angels was discussed. Our study aims to determine where Māturīdī places the angels in the hierarchy of existence, how he describes their existence, what views he has about their nature, and with what evidence he proves their existence. Māturīdī argues that there are many jawhars that we cannot see like angels, but whose existence we believe, and he states that Allah has not given humans the power to see the things of the invisible universe in the life of this world. He points out that the failure to see angels is not enough to judge their absence, and he reveals his opinion with rational inference. While proving the existence of angels, it also clarifies the subject by giving examples from the versicles. How Māturīdī proved the existence of angels is the main subject of this study. Kelâm literatüründe varlıklar, varlığının başlangıcı olmayan kadîm ve sonradan meydana gelen hâdis olmak üzere ikiye ayrılır. Kadîm; yaratılma, sonradan olma, doğma gibi özelliklere sahip olmayan Allah’ın kendisidir. Hâdis ise Allah’ın dışında her şeydir. Hâdis varlıklar latîf ve kesîf olmak üzere iki kısımda incelenir. İçinde yaşadığımız âlemi oluşturan kesîf varlıklar canlı-cansız, cansızlar da sıvı-katı şeklinde alt kümelere ayrılır. Bunlar fizikî yapıya sahip duyularla algılanabilir olduğu için bunların mevcûdiyetini tartışmak söz konusu değildir. Duyular ötesi âlemi oluşturan latîf varlıklar ise ulvî ve suflî olarak taksim edilmektedir. Melekler ulvî kısmındadır. Melekler kesîf varlıklar gibi görünmediği için varlığı hususunda ihtilaflar vardır. Melekler gayb âleminin varlıkları olduğu için duyu organlarımızla algılanamaz. Bundan dolayı deney ve tecrübe ile sonuca ulaşan pozitif bilimler meleklerin varlığı ve yokluğu ile ilgilenmez. Onlarla ilgili bilgiye Kur’an ve hadislerden ulaşırız. Kur’ân’da meleklerin varlığına inanma iman esasları arasında sayılmaktadır. Ayrıca hiçbir tesir altında kalmadan da sağlam akıl meleklerin varlığına hükmeder. Meleklerin varlığına inanma naslarla sabit olmakla birlikte varlıklarının ispatlanması konusunda bazı âlimler onların varlığını aklî delillerle ispatlamaya çalışırken bazıları da onların varlığının naklî delillerle sabit olduğu görüşündedir. Bu tebliğde, Ebû Mansûr el-Mâtürîdî’nin (ö. 333/944) Kitâbü’t-Tevhîd ve Te’vîlâtü’l-Kur’ân adlı eserleri merkeze alınarak onun meleklerin varlığına dair görüşü konu edinilmiştir. Çalışmamızın amacı, Mâtürîdî’nin varlık hiyerarşisinde melekeleri nereye konumlandırdığını, varlıklarını nasıl tarif ettiğini, mâhiyetleri hakkında hangi görüşlere sahip olduğunu ve hangi delillerle varlıklarını ispatladığını tespit etmektir. Mâtürîdî, melekler gibi göremediğimiz ama varlığına inandığımız pek çok cevherin olduğunu ileri sürmekte ve Allah’ın insanlara, dünya hayatında gayb âlemine ait şeyleri görebilme kudreti vermediğini belirtmektedir. O, meleklerin görülememesinin onların yokluğuna hükmetmek için yeterli olmadığına dikkat çekmekte ve bu görüşünü aklî çıkarımla ortaya koymaktadır. Meleklerin varlığını ispatlarken aynı zamanda âyetlerden de örnekler vererek konuya açıklık getirmektedir. Mâtürîdî’nin meleklerin varlığını nasıl ispatladığı bu çalışmanın temel konusudur.